2008
DOI: 10.1108/09578230810882027
|View full text |Cite
|
Sign up to set email alerts
|

Principals' opinions of organisational justice in elementary schools in Turkey

Abstract: Purpose -This study aims to present the opinions of public elementary school principals in Turkey about the current organisational justice practices among teachers from the distributive, procedural, interactional, and rectificatory dimensions. Design/methodology/approach -The opinions of 11 public elementary school principals in Ankara about organisational justice practices were identified through focus group and conceptual analyses. Findings -School principals are seen to distribute justice on matters like le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 23 publications
1
10
0
3
Order By: Relevance
“…In the analyses, it was found that teachers' perceptions of organizational justice were at a high level. The studies conducted on this subject also support the results of this study (Özer et al, 2006;Baş and Şentürk, 2011;Yaylacı, 2004;Atalay, 2005;Ünal, 2003;Tan, 2006;Polat, 2007;Aydın and Kepenekçi, 2008;Polat and Celep, 2008;Yılmaz and Taşdan, 2009;Titrek, 2009;Yılmaz, 2010;Oğuz, 2011;Gök, 2014;Kılıç andDemirtaş, 2015 andTerkeş, 2015). It was also found that organizational trust levels of teachers were at the moderate level.…”
Section: Sonuç Ve Tartişmasupporting
confidence: 83%
See 1 more Smart Citation
“…In the analyses, it was found that teachers' perceptions of organizational justice were at a high level. The studies conducted on this subject also support the results of this study (Özer et al, 2006;Baş and Şentürk, 2011;Yaylacı, 2004;Atalay, 2005;Ünal, 2003;Tan, 2006;Polat, 2007;Aydın and Kepenekçi, 2008;Polat and Celep, 2008;Yılmaz and Taşdan, 2009;Titrek, 2009;Yılmaz, 2010;Oğuz, 2011;Gök, 2014;Kılıç andDemirtaş, 2015 andTerkeş, 2015). It was also found that organizational trust levels of teachers were at the moderate level.…”
Section: Sonuç Ve Tartişmasupporting
confidence: 83%
“…Yapılan analizlerde öğretmenlerin örgütsel adalet algılarının yüksek düzeyde olduğu sonucuna ulaşılmıştır. Bu konuda yapılan çalışmalar bu araştırmanın sonucunu desteklemektedir (Özer ve diğ., 2006;Baş ve Şentürk, 2011;Yaylacı, 2004;Atalay, 2005;Ünal, 2003;Tan, 2006;Polat, 2007;Aydın ve Kepenekçi, 2008;Polat ve Celep, 2008;Yılmaz ve Taşdan, 2009;Titrek, 2009;Yılmaz, 2010;Oğuz, 2011;Gök, 2014;Kılıç ve Demirtaş, 2015;Terkeş, 2015). Diğer bir ifadeyle araştırmaya katılan öğretmenlere okullarında kendilerine karşı genelde adil davranıldığı, kurum içerisinde eşit davranıldığı sonucu elde edilmiştir.…”
Section: Sonuç Ve Tartişmaunclassified
“…On the other hand, strategies for protecting the past accomplishments involve organizational efforts to transform short-term legitimacy into long-term effort (Patriotta, Gond, & Schultz, 2011). In addition, despite the fact that it is primarily considered as one of a reactive strategy, making apologies and promises not to repeat the problems might satisfy stakeholders and serve as a protective strategy by resolving trust issues caused by instances of mismanagement (Aydın & Karaman-Kepenekçi, 2008).…”
Section: Strategic Approachmentioning
confidence: 99%
“…On the basis of descriptive criteria a distinction can be made between schools that are socially just and those that are not. Some of the attributes of schools that are unjust entities are that they expose members of the school community to inequalities and hurtful experiences of injustice [4], restrict freedom and inflict psychological harm through exposure to racist words, hate speech and, social oppression [3] and, allocate resources unequally thus engendering resentment, resistance, discipline problems and student low self-esteem [6]. On the other hand, schools that are socially just promote inclusion and equity, hold high expectations for all learners, develop reciprocal community relationships, and have direct social justice education and intervention [8].…”
Section: Conceptual Framework and Related Literaturementioning
confidence: 99%